Reliability of “Modified timed up and go” test in children with cerebral palsy - Dhote, Sanjivani N. (Medknow Publications & Media Pvt Ltd, 2012)
BACKGROUND: Timed up and go (TUG) is a quick test used in clinical practice as an outcome measure to assess functional ambulatory mobility or dynamic balance in adults. However, little information is available on TUG test used in cerebral palsy. Hence, the purpose of our study was to assess the intra-rater reliability of TUG test in cerebral palsy children. AIM AND OBJECTIVE: To assess within–session and test-retest reliability after 1 week of TUG test in cerebral palsy children. Setting and Design: It was an a cross-sectional observational study conducted in a neurorehabilitation unit, with 30 cerebral palsy children of 4–12 years, within Gross Motor Function Classification System (GMFCS) level I, II, III, and with an IQ ≥50.The sampling technique used was purposive sampling excluding children with cognitive deficit. MATERIALS AND METHODS: Subjects performed TUG on three occasions – Initial assessment (time 1), 30 min after initial assessment (time 2), and 1 week after initial assessment (time 3). Three trails were conducted for each of the three occasions. The mean score of three trials was documented as the final score. Within-session and test–retest reliability were analyzed using scores of time 1 and 2, and time 1 and 3, respectively. STATISTICAL ANALYSIS: The documented data were analyzed for within-session and test–retest reliability after 1 week of TUG test by using intraclass correlation coefficient (ICC). RESULTS: Reliability of TUG test was high, with ICC of 0.99 for within-session reliability and 0.99 for test–retest reliability. CONCLUSION: Intra-rater reliability of TUG test in cerebral palsy children was found to be high.